Multi-criteria evaluation for the sustainable use of loess gullies in rural–urban borderline - Jan Rodzik; Beata Żuraw; Barbara Sowińska-świerkosz; Jakub Kuna; Małgorzata Sosnowska; Marek Podsiedlik (Scientific Reports)
Abstract The paper explores the issue of sustainable use of urban gullies under the pressure of suburbanization. The objective of this study was to provide guidelines for land restoration in relation to the Polish case study by analyzing (1) land cover changes, (2) their impact on the geomorphic evolution of gullies and (3) valuable plant associations. To this end, GIS technologies, identification of soil and sediments and valorization of plant associations were adopted to capture the total set of impacts. The findings revealed that land cover change indicators combined with geomorphological and plant aspects are useful for assessing the state of gully development and, on this basis, for providing revitalization recommendations. Long-lasting anthropogenic modifications were the main driving factors of gully development and exhibited significant interrelationships among all the indicators. This study revealed the need for strengthening the recreational use of gullies through multifunctional use by different citizen groups and for simultaneous protection of gullies in terms of geological and ecological aspects. This direction of action enables gully development and use in accordance with the sustainable development concept, which focuses on equal economic growth that generates wealth for all without harming the environment.